Analysis of Public Trust in The Government on The Importance of Injecting The Covid-19 Vaccine in Aceh - Zamharira, Cut; Muqni Affan Abdullah (Jurnal Administrasi Publik (Public Administration Journal), 2023)
This article aims to explain what efforts have been made by the Aceh Health Service to build public confidence in the importance of injecting the COVID-19 vaccination. The low coverage of the COVID-19 vaccination in Aceh as of 18 September 2021, which was only 11.74%, made Aceh one of the 3 regions with the lowest COVID-19 vaccination rate in Indonesia, until the end of November 2021. Many people refused to get vaccinated because the background of mistrust was the reason for the low coverage of the COVID-19 vaccination in Aceh at that time. However, since the end of December 2021, the coverage of Covid-19 vaccinations in Aceh has begun to increase, so that in February 2022 Aceh is ranked 18th nationally. This study uses a descriptive qualitative approach through interviews, observation, and documentation techniques. The results of the study show that public trust sought by the Aceh Health Service, Banda Aceh City Health Office, and Sabang City increases when people benefit from programs carried out by the government as explained by J. M. Lewis in Mohammad Thahir (2020), If the community benefits from programs carried out by the government, then public trust will increase.